Advances in cardiology - Chatterjee, Kanu (Jaypee Brothers Medical Publishers, 2014)
Advances in cardiology is a bold adventure by the editors. In the last few years,there has been enormous advances in many aspects of cardiology. However, only in a very few fields, there have been extraordinary advances.